National Culture and Culinary Exploration: Japan Evidence of Heterogenous Moderating Roles of Social Facilitation - Bin Liu (Frontiers Media S.A., 2021)
This article explores the role of national culture in the culinary consumption behavior of international tourists and the moderating influence of different types of travel companions. Study 1 adopted a text-mining, topical modeling approach to process useful reviews (n = 7,803) posted at TripAdvisor by users from 86 countries. Study 2 develops and tests a conceptual model of the relationships between national culture and culinary choices including culinary types and range of culinary choices, based on a secondary dataset of large-scale surveys from the tourism authority of the destination containing 9,141 responses by tourists from over 60 countries or regions. The results reveal that both Uncertainty Avoidance and Individualism-Collectivism have significant effects on tourist food consumption categories and the range of culinary choices. The study also evaluated the role of the moderating effect of travel companions, and results supported the significant relationship on the range of culinary choices when the tourists were accompanied by different types of travel companions.